PENERAPAN KONTEKS BUDAYA DALAM PSIKOMETRIKA - Andidar, Denestyar Rizki; Prahastuti, Nurul F (JURNAL TALENTA PSIKOLOGI, 2021)
The purpose of the study was to explain the meaning of the culture itself that has always been attached to the individual. An ideal measurement instrument is one that distinguishesone particular characteristic of an individual from another, and is accompanied by its inclusion. However, not everything in culture can be applied to psychometric studies, to avoid this irrelevance, researchers ask the fundamental question, namely what psychometric and cultural meanings are so that both are important to be applied in research and applicable professional work. This research is useful to be a reference because it discusses the fundamentals of the importance of paying attention to cultural contexts that rarely get attention in the field of psychometrics. The results of the study stated that in order for measurements to reach an accurate and relevant level, a process of conceptualizing measuring instruments that are culturally fair. , considering that a psychological measuring tool is used in various areas of research, diagnostic, selection, etc.